Acute effects of BCAA supplementation on some biochemical indicators and the performance of long-distance runners - Stochero, C. M.; Gomes, P. S. (Medicine & Science in Sports & Exercise, 1997)
The effects of BCAA supplementation (Leucine, Isoleucine, and Valine) - 200 mg/kgBW on time to exhaustion, blood lactate, and serum urea concentration during an exhausting run at 85%VO2peak were evaluated. Ss (N = 10) were experienced long-distance runners. Two trials, a placebo condition and a supplementation condition, were performed one week apart under standardized preparatory conditions. It was found that supplementation of BCAA prior to long-distance runs of less than 90 minutes duration at an intensity of 85%VO2peak did not function as an ergogenic aid. Implication. BCAA supplementation does not increase performance in an exhausting long-distance run.